2015
DOI: 10.3758/s13414-015-0880-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cues derived from statistical patterns can overcome resource limitations in the attentional blink

Abstract: Previous studies have shown that humans are sensitive to statistical patterns indicating the likely locations, identities, and timings of visual targets. Here we tested whether participants can also use this kind of information to ameliorate the attentional blink (AB)-a reduction in accuracy for the second of two targets (T1, T2) presented at brief intertarget intervals (lags). In particular, we asked whether participants can use patterns arising from differential distributions of intertarget lags across trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 57 publications
4
25
0
Order By: Relevance
“…This more sensitive measure also revealed benefits linked to target probability-however, these benefits were relatively small and only occurred when probability varied by approximately .25 across conditions. The present work replicates the findings of Visser et al (2015) using T2 accuracy as a dependent measure. This provides additional evidence that probability can serve as strong temporal cue as long as differences in probability are sufficiently salient.…”
Section: Relationship To Temporal Cuingsupporting
confidence: 67%
“…This more sensitive measure also revealed benefits linked to target probability-however, these benefits were relatively small and only occurred when probability varied by approximately .25 across conditions. The present work replicates the findings of Visser et al (2015) using T2 accuracy as a dependent measure. This provides additional evidence that probability can serve as strong temporal cue as long as differences in probability are sufficiently salient.…”
Section: Relationship To Temporal Cuingsupporting
confidence: 67%
“…Other studies, however, have demonstrated that the temporal information that reduces T2 detection deficits can be learned from experience under appropriate conditions (Shen & Alain, 2012; Visser et al, 2015). Shen and Alain (2012) used an auditory version of the attentional blink task and block-wise manipulated the relative probability (80% or 20%) of a short T2 lag (lagging 2 items from T1) and a long T2 lag (lagging 8 items from T1).…”
Section: Introductionmentioning
confidence: 99%
“…In general, when the timing of T2 relative to T1 was predictable, attentional blink was attenuated (e.g., Martens & Johnson, 2005; Shen & Alain 2011; 2012; Visser, Ohan, & Enns, 2015; Visser, Tang, Badcock, & Enns, 2014). In particular, Martens and Johnson (2005) compared the effects of the learning and the explicit knowledge of the likely T1-T2 interval on the attenuation of attentional blink.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations